ВПЛИВ ЦИФРОВОЇ ЕКОНОМІКИ НА ТЕНДЕНЦІЇ СУЧАСНОГО РИНКУ ПРАЦІ - Liubov, Vodianka; Kharovska, Angelina (Дніпровський державний аграрно-економічний університет, Видавництво ТОВ "ДКС-Центр", 2022)
The article considers the current problem of the impact of the digital economy on nature and the development of the modern labor market. There are identified three groups of approaches to the interpretation of the concept of "digital economy" and outlined the main theories of each approach. Synonyms for the term "digital economy" used by scientists in modern world literature are proposed. There are three groups of consequences caused by society's transition to the digital economy, and they are briefly described. A description of the new employment model "Work 4.0", the emergence of which is due to the transition to the fourth industrial revolution "Industry 4.0". The tendencies of the modern labor market caused by the rapid development of the economy are singled out and analyzed in detail. The problem of automation and robotics and its consequences, which both employers and workers have already faced, are described, what is more, the situation will only worsen over time, including rising unemployment, lack of highly qualified specialists, maladaptation of education to rapid changes in the labor market requirements. Even though there are undoubtedly positive consequences of the robots' implementation in the work process and increase the level of production's automation. New forms of non-standard work, which formed under the influence of the active development of innovation processes and economic transformation in the twentieth century, are singled out. The necessity of the formation of new labor relations and labor ethics is substantiated. The reason "workplace" nature's transformation and the active introduction of telework in employment is explained. Modern IT tools and Internet platforms used in the market today are described briefly. The terms "digital labor market" and "digital employment" are defined and should be used in terms of the characteristics of the modern labor market and its prospects. The positive and negative impact of the COVID-19 pandemic on the modern labor market have been analyzed, as well as the changes it has led to. It is concluded that digital technologies change the individual's existence as a business entity, transferring economic activity from the material to the virtual. The study shows that the digital economy transforms the classic relationship between the employer and employee, attitude to work, working conditions.
Influence of the digital economy on the trends of the modern labor market
Keywords: цифрова економіка; ринок праці; цифровізація; автоматизації; роботизація; цифровий ринок праці; цифрова зайнятість